The quick fix guide to academic writing - Shon, Phillip C. (Los Angeles SAGE, 2018)
Providing you with a quick set of writing rules to follow, this tried and tested guide uses a unique and easy to follow grid-based system. Packed with advice on understanding (big and little) common errors made in academic writing, it helps you identify patterns in your own writing and demonstrates how to reshape or re-evaluate them - and raise your writing game in any academic context.
Keywords: Academic writing; REFERENCE / Writing Skills; Literature; Academic writing; Literature